New-onset refractory status epilepticus: A retrospective cohort study. (January 2020) - Gugger, James J.; Husari, Khalil; Probasco, John C.; Cervenka, Mackenzie C.
Highlights: NORSE is associated with prodromal febrile illness and inflammatory CSF profile. Regional hypermetabolism is a common finding on FDG-PET in NORSE. The majority of patients had no clear etiology identified after extensive evaluation. Immunotherapy and the ketogenic diet are feasible treatments for NORSE. NORSE is associated with high mortality and drug-resistant epilepsy. Abstract: Purpose: To describe the clinical, laboratory, neuroimaging, electroencephalographic features, etiology, treatment, as well as short-term and long-term outcomes of adults with new-onset refractory status epilepticus (NORSE). Method: A retrospective, single institution cohort study (2010–2018) of consecutive adult patients with NORSE. Results: Among 20 patients with NORSE, nine (45 %) had prodromal febrile illness, 12 (60 %) had evidence of inflammation on CSF profile. Six patients (30 %) met criteria for definite autoimmune encephalitis (AE) while 8 patients (40 %) had probable AE. Eleven out of 13 (85 %) patients had an abnormal FDG-PET scan with the most common finding being regional hypermetabolism. Fourteen patients (70 %) received immunotherapy and ten (50 %) received the ketogenic diet (KD). Fifteen patients (75 %) progressed to super-refractory status epilepticus (SRSE) and seven patients (35 %) died in the hospital or within six months of discharge. Among the surviving patients, eight (40 %) had a good outcome (i.e., modified Rankin Scale score 0–2); 12 (80 %) received a diagnosis of epilepsy of which nine (75 %) developed drug-resistant epilepsy. Conclusions: New-onset refractory status epilepticus is a syndrome associated with multiple complications, high mortality, and subsequent intractable epilepsy. There are multiple causes, some of which are autoimmune encephalitides; however, in this series the majority of patients had no clear etiology identified after extensive evaluation. Prospective studies are needed to determine optimal evaluation and treatment.